Characterization of SrCO3 and BaCO3 nanoparticles synthesized by sonochemical method - Thongtem T. (2014)
SrCO3 and BaCO3 nanoparticles were synthesized using Sr(NO3)2 or Ba(NO3)2 and Na2CO3 as starting materials in ethylene glycol by ultrasonic irradiation at 80 °C for 1-5 h. Their phases, vibration modes and morphologies were characterized using X-ray powder diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, selected area electron diffraction (SAED) and transmission electron microscopy (TEM). These products were found to be orthorhombic SrCO3 and BaCO3 nanoparticles with 20-50 nm and 40-100 nm ranges, respectively. Asymmetric stretching, symmetric stretching, and out of plane and in plane bending vibrations of CO32- complexes were also detected. © 2009 Elsevier B.V. All rights reserved.